Dimensional check of weld neck flange based on ASME B16.5 - Ritonga, Fatima Sari; Purba, Adi Syahputra; Simanjuntak, Jefri Kemri Rodi Samuel; Fadilah, Nurul; Amalia, Mutia (International Journal of Mechanical Computational and Manufacturing Research, 2025)
This study aims to verify that the dimensions of a weld neck flange conform to ASME B16.5 standards. The flange used is a raised face type made of carbon steel ASTM A105N with 16-inch NPS, selected for its corrosion resistance, and welded with UNS 006625, a nickel-rich alloy that enhances corrosion protection. Dimensional checks were performed on five samples, each measured three times, using both visual inspection and measuring tools, including a roughness comparator and vernier caliper. Key dimensions measured include outside diameter (705 mm, tolerance +4 mm/-1 mm), inside diameter (333.3 mm, ±1.5 mm), bolt circle diameter (616 mm, ±1.5 mm), flange thickness (88.90 mm, +3 mm), and hub thickness (30.43 mm post-welding, with tolerance not less than 12.5% of pipe wall thickness) the visual inspection assessed surface roughness within the acceptable range of 3.2 µm to 6.3 µm. The inspection results showed that all measured dimensions were within the permissible limits, confirming that the weld neck flange meets the requirements of ASME B16.5.